Resource potential of Beninese soils for maize cultivation - Rodrig S. Kakpo; Igor Yu. Savin (Бюллетень Почвенного института им. В.В. Докучаева, 2021)
Due to the growth of the population, the need of the Republic of Benin to increase food production is growing significantly. Maize is the main cultivated crop in the country, being also the main item of nutrition. The scientific rationale for expanding the area of maize cultivation is an important economic task. GIS database was created, which includes all the necessary information on soil, relief, and climate conditions in the country for assessment the resource potential of lands for maize cultivation. Geoinformation modeling of soil and land suitability for maize cultivation was performed. The most suitable lands were identified. Possibility to expand areas for maize cultivation in the country was assessed. It was found that the largest resources (in parts of the land fund) for the expansion of maize cultivation are in the following communities of Benin: Tory-Bossito (96%), Toviklin (92.41%), Materi (90.31%), Kobli (89.25%), Wayogbe (87.99), Parakou (86.57%), Jaco-Tomey (85.66%), Avrankou (85.46%), Allada (84.13%), Bohicon (82.24%), Sakete (81.85%), Za Kpota (78.08%), Akpo Misserete (77.96%), Bopa (77.15%), Kpomasse (75.82%) and Ifania (75.03%). The findings led us to conclude that, theoretically, the gross maize production in Benin could be increased fivefold (from 1,514,913 tons to 5,513,947 tons) only by expanding the cultivation area.